TA’LIL AL-AHKAM (THE LEGAL ANALOGY) BETWEEN HARTA PUSAKO TINGGI IN MINANGKABAU AND WAQF - Hanif A'la Ilhami; Busyro Busyro; Ikhwan Ikhwan (Hukum Islam, 2026)
This research examines the position of harta pusako tinggi in Minangkabau and the process of ta’lil al-ahkam in relation to waqf property, identifying the similarities and differences between the two. The research employs a qualitative approach, utilizing library sources and interviews, which are then formulated through inductive and deductive reasoning. The findings indicate that Minangkabau scholars analogize harta pusako tinggi to waqf, with particular emphasis on the aspect of legal validity (the permissibility of its utilization). Harta pusako tinggi and waqf are not entirely identical; rather, they share many similarities while also exhibiting several differences. Nevertheless, these differences do not hinder the validity of the analogy. From the perspective of ta’lil al-ahkam, waqf functions as the ashl (principal case), while harta pusako tinggi constitutes the furu‘ (derivative case). The ‘illah underlying this analogy is the characteristic of al-ḥabs, namely the practice of restraining property so that it may provide long-term benefits and prevent various forms of taṣarruf (disposal or transfer) over it. The legal ruling of the ashl is the permissibility of its utilization and legal legitimacy; such property may be used and continuously transmitted to subsequent generations in accordance with the established system. This form of analogy serves as a rebuttal to views that prohibit the utilization of harta pusako tinggi and, instead, reinforces its existence, continuity, and protection from extinction. In this regard, the concepts inherent in waqf can contribute to refining and complementing the existing regulations governing harta pusako tinggi.